How to escape the nexus of climate change, conflict and forced displacement: From fragility to stability - Goldberg, Mark Leon; Birner, Jana; Mwanza, Barthelemy; Craparo, Alessandro (2024)
This episode is produced in partnership with the CGIAR Research Initiative on Fragility, Conflict, and Migration for a series that examines what works to improve the well-being of people in Fragile and Conflict Affected Settings. CGIAR is a global partnership that unites international organizations engaged in research about food security. We are calling this series “From Fragility to Stability” and in today’s episode I host a roundtable discussion with three experts about how to escape the nexus of climate change, conflict and forced displacement